How native-like can you possibly get: fMRI evidence for processing accent - Ghazi-Saidi, Ladan; Dash, Tanya; Ansaldo, Ana I. (Frontiers in Human Neuroscience, 2015)
Introduction: If ever attained, adopting native-like accent is achieved late in the learning process. Resemblance between L2 and mother tongue can facilitate L2 learning. In particular, cognates (phonologically and semantically similar words across languages), offer the opportunity to examine the issue of foreign accent in quite a unique manner. Methods: Twelve Spanish speaking (L1) adults learnt French (L2) cognates and practiced their native-like pronunciation by means of a computerized method. After consolidation, they were tested on L1 and L2 oral picture- naming during fMRI scanning. Results and Discussion: The results of the present study show that there is a specific impact of accent on brain activation, even if L2 words are cognates, and belong to a pair of closely related languages. Results point that the insula is a key component of accent processing, which is in line with reports from patients with foreign accent syndrome (FSA) following damage to the insula (e.g. Moreno-Torres et al., 2013; Katz et al., 2012; Tomasino et al., 2013), and healthy L2 learners (Chee et al., 2003). Thus, the left insula has been consistently related to the integration of attentional and working memory abilities, together with fine-tuning of motor programming to achieve optimal articulation.